Exploration of chitosan and its modified derivatives as vaccine adjuvant: A review - Girish Kumar; Tarun Virmani; Shashi Kiran Misra; Ashwani Sharma; Kamla Pathak (Carbohydrate Polymer Technologies and Applications)
Chitosan is a natural polysaccharide that has earned much credit in the pharmaceutical field due to its broad implementation in drugs, antigens, and vaccine delivery. Owing to unique characteristics of biocompatibility, biodegradability, mucoadhesiveness, and less toxicity, chitosan holds promise as a vaccine adjuvant or vaccine delivery system. Furthermore, chitosan exhibits antiviral properties making it an ideal vaccine adjuvant and carrier for the delivery of vaccine. The presence of ridiculous functional groups in the parent structure of chitosan enables the creation of modified chitosan derivatives having improved physiochemical properties which provide enhanced vaccine adjuvant properties of chitosan. This review summarizes the potential of chitosan and its modified derivatives as an antiviral agent and vaccine adjuvant along with patents related to the application of chitosan as a vaccine adjuvant and vaccine carrier.